The Flue Gas Desulfurization Gypsum Applications in Production of Eco-Friendly Cementitious Matrices - Bibiano, R. H. N.; Izidoro, Juliana de Carvalho; Fungaro, Denise Alves (Journal of Applied Materials and Technology, 2023)
Portland cement is one of the most manufactured materials in the world. The worldwide cement industry accounts for at least 5-8% of the anthropogenic CO2 emissions and therefore is an important sector for CO2-emission mitigation strategies to limit global warming. One of the strategies for reducing the carbon footprint of the cement industry is replace traditional Portland cement with other solid wastes. In the present study, the influence of the application of flue gas desulfurization gypsum (FGD gypsum) generated from coal-fired power plant in construction mortar was investigated. Cylindrical specimens were molded with Portland cement type CPII-F 32, sand and 0%, 25%, 50% and 75% amounts of FGD gypsum. After curing time of 1, 3, 7, 28 and 91 days, the cementitious materials were characterized mechanically by axial compressive strength, setting time and slump. The pastes in the age of 28 days were further characterized by X-ray diffraction with Rietveld analysis. Results showed that FGD gypsum can be used as a substitute for cement as a setting retarder in an amount of up to 25%, and as an accelerator in an amount of 75%, being necessary dosage of the specific traces of the materials depending on the purpose of its use.